2022
DOI: 10.1002/ddr.22009
|View full text |Cite
|
Sign up to set email alerts
|

Dioscin induces osteosarcoma cell apoptosis by upregulating ROS‐mediated P38 MAPK signaling

Abstract: Osteosarcoma is the most common primary malignant bone tumor in children and adolescents. Many patients with osteosarcoma readily develop resistance to chemotherapy and have an extremely dismal prognosis. Dioscin, a saponin, is known to exhibit potent anticancer activities and induce cellular death of a variety of cancer types. However, the inhibitory effect of dioscin on osteosarcoma cells and its underlying mechanisms have not been fully elucidated. We investigated the responses of human U2‐OS and MG63 osteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
(40 reference statements)
0
9
0
Order By: Relevance
“…Among many signaling pathways, MAPK signaling pathway plays a particularly important role in cell proliferation, differentiation, apoptosis, angiogenesis and tumor metastasis [ 29 ]. There is reported that dioscin induces OS cell apoptosis by upregulating ROS-mediated P38 MAPK signaling [ 30 ], and Fan’s research also showed that siglec-15 promotes tumor progression in OS via DUSP1/MAPK pathway [ 31 ]. Similarly, the role of PI3K/AKT pathway in reversing drug resistance in OS is confirmed by the examination of some reports [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among many signaling pathways, MAPK signaling pathway plays a particularly important role in cell proliferation, differentiation, apoptosis, angiogenesis and tumor metastasis [ 29 ]. There is reported that dioscin induces OS cell apoptosis by upregulating ROS-mediated P38 MAPK signaling [ 30 ], and Fan’s research also showed that siglec-15 promotes tumor progression in OS via DUSP1/MAPK pathway [ 31 ]. Similarly, the role of PI3K/AKT pathway in reversing drug resistance in OS is confirmed by the examination of some reports [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…U2OS, HOS [134] Fistein Wood wax U2OS [135] Ginsenoside Rh2 Panax ginseng C. A. Mey. U2OS [136] MAPK pathway Dioscin Dioscorea polystachya Turczaninow MG-63, U2OS [137] Lycorine Lycoris radiata (L'Her.) Herb.…”
Section: Mg-63mentioning
confidence: 99%
“…Zheng et al [137] found that diosgenin inhibited the proliferation, migration and invasion of OS cell, and induced OS cell apoptosis by up-regulating ROS-mediated P38/MAPK signaling pathway. Similarly, studies by Ning L, Yuan XH et al [97,138] found that lycorine was also able to increase the intracellular ROS content, thereby activating the p38-MAPK signaling pathway and inhibiting the expression level of the downstream member p53 protein, which in turn arrested the growth of mouse OS cells in G1 phase, and promoted apoptosis of mouse OS cells.…”
Section: Targeted Therapy Of Os By Signaling Cascade Associated With ...mentioning
confidence: 99%
“…N-acetylcysteine is an inhibitor of ROS that can inhibit the apoptosis of diosgenin-related p38/MAPK signal transduction. This indicates that ROS plays an important role in diosgenin-induced apoptosis ( Zheng et al, 2023 ). In addition, the class I HDAC inhibitor MS-275 enhances the vulnerability of ROS in sarcoma cells.…”
Section: Therapeutic Prospect Of Targeting Hif-1α In the Treatment Of...mentioning
confidence: 99%